F (x) = 4x-3 및 g (x) = 3x + 1 일 때 f (x) * g (x)는 무엇입니까?

F (x) = 4x-3 및 g (x) = 3x + 1 일 때 f (x) * g (x)는 무엇입니까?
Anonim

대답:

아래의 솔루션 프로세스를 참조하십시오.

설명:

(xx) * g (x) = (색상 (빨강) (4x) - 색상 (빨강) (3)) xx (색상 (파랑) (3x) + 색상 (파랑) (1)) #

#f (x) * g (x) = (색상 (빨강) (4x) xx 색상 (파랑) (3x)) + (색상 (빨강) (4x) xx 색상 (파랑) (1) 빨간색) (3) xx 색 (파란색) (3x)) - (색 (빨간색) (3) xx 색 (파란색)

#f (x) * g (x) = 12x ^ 2 + 4x - 9x - 3 #

#f (x) * g (x) = 12x ^ 2 + (4 - 9) x - 3 #

#f (x) * g (x) = 12x ^ 2 + (-5) x - 3 #

#f (x) * g (x) = 12x ^ 2 - 5x - 3 #